45 REGULATION OF 4-HYDROXY-2-NONENAL-MEDIATED ENDOTHELIAL BARRIER FUNCTION BY FOCAL ADHESION AND ADHERENS JUNCTION PROTEINS. (1st March 2006) - Usatyuk, P. V.; Natarajan, V.
Abstract : 4-Hydroxy-2-nonenal (4-HNE), a highly reactive aldehyde generated by peroxidation of membrane lipids, altered endothelial cell (EC) barrier function, resulting in vascular leakiness. Here we report that 4-HNE mediates EC barrier dysfunction by modulating focal adhesion and adherens junction proteins that affect cell-cell and cell-matrix interactions via integrins. Treatment of bovine lung microvascular endothelial cells (BLMVECs) with 4-HNE, in a dose-dependent manner, modulated cell-cell adhesion contacts, enhanced intracellular ROS formation, and increased permeability. Interestingly, 4-HNE did not alter cell-matrix interactions as determined by transendothelial electrical resistance measurement. Therefore, we hypothesized that 4-HNE-induced permeability changes involved modulation of focal adhesion and adherens junction proteins. Treatment of BLMVECs with 4-HNE resulted in the redistribution of FAK, b-catenin, paxillin, VE-cadherin, and ZO-1 and caused intercellular gap formation. Western blot analyses confirmed that 4-HNE formed Michael adducts with the focal adhesion and adherens junction proteins. Furthermore, 4-HNE decreased tyrosine phosphorylation of FAK without affecting total cellular FAK contents. Flow cytometry and fluorescent microscopy analyses revealed a time-dependent reduction in the surface integrins after 4-HNE treatment. Conclusion: These results indicate that 4-HNE affects EC permeability by modulating cell-cell adhesion involving focal adhesion, adherens and tight junction proteins, as well as integrins signal transduction. Supported by NIH RO1 HL 69909 and P01 HL 58064 to V.N.